Molecular and nonmolecular diagnostic methods for invasive fungal infections - Arvanitis, Marios; Anagnostou, Theodora; Fuchs, Beth Burgwyn; Caliendo, Angela M; Mylonakis, Eleftherios (Clinical microbiology reviews, 2014)
Invasive fungal infections constitute a serious threat to an ever-growing population of immunocompromised individuals and other individuals at risk. Traditional diagnostic methods, such as histopathology and culture, which are still considered the gold standards, have low sensitivity, which underscores the need for the development of new means of detecting fungal infectious agents. Indeed, novel serologic and molecular techniques have been developed and are currently under clinical evaluation. Tests like the galactomannan antigen test for aspergillosis and the β-glucan test for invasive Candida spp. and molds, as well as other antigen and antibody tests, for Cryptococcus spp., Pneumocystis spp., and dimorphic fungi, have already been established as important diagnostic approaches and are implemented in routine clinical practice. On the other hand, PCR and other molecular approaches, such as matrix-assisted laser desorption ionization (MALDI) and fluorescence in situ hybridization (FISH), have proved promising in clinical trials but still need to undergo standardization before their clinical use can become widespread. The purpose of this review is to highlight the different diagnostic approaches that are currently utilized or under development for invasive fungal infections and to identify their performance characteristics and the challenges associated with their use.